Principal component analysis of time delay in large IP network - Xuan WEI; Xiaoying HUANG (Dianxin kexue)
Network time delay is one of the key indexes to evaluate network performance.Principal component analysis (PCA) is a kind of multivariable analysis and declination algorithm commonly used in the field of data mining.Based on PCA analysis of time delay in large IP networks, aiming to find out the deep reason of time delay and the interdependencies among nodes of the network, a scientific and reasonable network time delay evaluation system was built, and effective suggestions for IP network construction and optimization were finally got.The off-line analysis of the historical network delay is only a preliminary application of the PCA.In the future, PCA can be applied to the real-time on-line monitoring and analysis of the network performance, such as network traffic, network delay, network packet loss, etc., in combination with the network topology, current network traffic direction, routing, distance and other related factors, thus the efficiency and quality of network operations can be further improved.